Study of the Structure of a Surface-porous Adsorbent using the Gas Chromatographic Version of the Molecular Probe method - Yu.I. Tarasevich; A.I. Zhukova; E.V. Aksenenko; S.V. Bondarenko; O.V. Nazarenko (Adsorption Science & Technology)
Results are presented of structural studies of a silica-based surface-porous adsorbent. It is shown that a reliable estimate of the size of the surface micropores of this adsorbent can be obtained using the gas chromatographic version of the molecular probe method. This is based on a comparison of the thermodynamic properties for the adsorption of substances of known molecular size on the surface-porous adsorbent with those characteristic for the adsorption of the same substances on to a non-porous adsorbent of a similar chemical nature.